PENGARUH TARIF PAJAK, KEPEMILIKAN ASING, LEVERAGE, DAN MEKANISME BONUS TERHADAP TRANSFER PRICING (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2021) - Anita Pranawasari Purba; Eka Hariyani; Rezi Abdurrahman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2026)
This study aims to analyze the effect of tax rates, foreign ownership, leverage, and bonus mechanisms on transfer pricing in manufacturing companies listed on the Indonesia Stock Exchange during 2019-2021. Transfer pricing is a pricing policy in transactions between related parties that may be used to minimize tax burdens and optimize company profit. This research uses a quantitative approach with secondary data obtained from annual reports published through the Indonesia Stock Exchange website and official company websites. The sample was selected using purposive sampling, resulting in 30 manufacturing companies with 90 firm-year observations, which were reduced to 40 observations after the outlier treatment. The data were analyzed using multiple linear regression with SPSS 30. The results show that tax rates, foreign ownership, leverage, and bonus mechanisms have a positive and significant effect on transfer pricing. The coefficient of determination (R²) is 22.8%, indicating that the independent variables explain 22.8% of transfer pricing, while the remaining 77.2% is explained by other variables outside this research model. Keyword: tax rates; foreign ownership; leverage; bonus mechanisms; transfer pricing